Justice Brokers: Examining Women’s Rights in the Polygamy Process in Gorontalo City - Muhammad Syakir Al Kautsar; Ajub Ishak; Nurul Mahmudah; Elfa Murdiana (Sakina: Journal of Family Studies, 2026)
The protection of women’s rights in the process of polygamy in Gorontalo City is a crucial issue that requires careful examination to emphasize the fundamental objectives of Islamic law. Legal protection represents an important manifestation of Islamic law’s goals in realizing justice, public welfare, and the protection of individual rights, particularly those of women. In this context, attention is directed to the preventive role of the Religious Court as well as the potential negligence of justice intermediaries (justice brokers) in prioritizing the protection of women’s rights, which can be analyzed through the perspective of maqāṣid al-sharī‘ah. Using the maqāṣid al-sharī‘ah framework, this study evaluates whether polygamous practices in Gorontalo City fulfill the objectives of Islamic law, including the protection of religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), lineage (ḥifẓ al-nasl), and property (ḥifẓ al-māl). The findings indicate that several challenges remain in both regulatory structures and practical implementation, particularly regarding weak verification mechanisms, unequal power relations within families, and the limited role of justice brokers in ensuring that women’s rights are fully considered during the legal process. From the perspective of justice theory proposed by John Rawls, the protection of women’s rights requires fairness in access to information and equal bargaining positions in decision-making. When the first wife lacks adequate information or experiences pressure to consent to polygamy, the process fails to meet the principle of justice as fairness. Therefore, strengthening the role of the Religious Court, improving oversight of justice brokers, and ensuring transparency in legal information are essential steps toward protecting women’s rights and achieving justice in polygamous practices.